1995
DOI: 10.1021/j100020a002
|View full text |Cite
|
Sign up to set email alerts
|

An I* laser pumped by NCl(a1.DELTA.)

Abstract: Pulsed I*(52P~/2) -I(52P3/2) lasing pumped by energy transfer from excited NCl(a'A) was observed in experiments in which iodine atoms and NC1 were produced by photodissociation of CHJ2 and ClN3, respectively. The inversion among the iodine atoms is pumped by NCl(a'A) generated in the chain decomposition of CIN3, rather than by excited NCl produced in the initial photodissociation. A kinetic model for the system which includes the energy transfer process, the chain decomposition of the azide, and I* loss proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 4 publications
0
44
0
Order By: Relevance
“…We note the branching fraction of ground state I( 2 P 3/2 ) from CH 2 I 2 is g 0.95 at the 193 nm photolysis wavelength. 19 Further, Ray and Coombe 8 have concluded that the secondary photolysis CH 2 I is not a significant source of I( 2 P 1/2 ) emission at 193 nm. Figure 9a shows the I( 2 P 1/2 ) emission time profile resulting from the photolysis 193 nm of only CH 2 I 2 at a density of 2.2 × 10 14 molecules/cm 3 and a laser fluence of 210 mJ/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note the branching fraction of ground state I( 2 P 3/2 ) from CH 2 I 2 is g 0.95 at the 193 nm photolysis wavelength. 19 Further, Ray and Coombe 8 have concluded that the secondary photolysis CH 2 I is not a significant source of I( 2 P 1/2 ) emission at 193 nm. Figure 9a shows the I( 2 P 1/2 ) emission time profile resulting from the photolysis 193 nm of only CH 2 I 2 at a density of 2.2 × 10 14 molecules/cm 3 and a laser fluence of 210 mJ/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…7 Recently, an NCl(a 1 ∆) to I( 2 P 3/2 ) energy transfer laser was demonstrated from the photolysis of chlorine azide (ClN 3 ) and CH 2 I 2 gas mixtures at 193 nm. 8 For NCl(a 1 ∆) to be practical as an energy source in chemical lasers, several issues need to be understood. These include the generation of high NCl(a 1 ∆) densities, determination of absolute NCl(a 1 ∆) concentration, identification of NCl(a 1 ∆) quenching species and their temperature-dependent rate constants, total rate constant and branching fraction, and the transfer rates to the laser candidate species.…”
Section: Introductionmentioning
confidence: 99%
“…Like O 2 (a 1 ), NCl(a 1 ) can be used in iodine lasers [8,9] where energy is transferred from the excited NCl molecules to I 2 . This chemically driven process is preferable to the use of O 2 (a 1 ) as NCl(a 1 ) is product of gas precursors, whereas the production of O 2 (a 1 ) through a chemical reaction involves bubbling Cl 2 though a solution [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ray and Coombe 2 have demonstrated a similar laser using metastable NCl(a 1 ∆) in place of O 2 (a). Also Du and Setser 3 have observed that addition of I 2 to metastable NF(a 1 ∆), which is more energetic than either NCl(a) or O 2 (a), increases the yield of the still more energetic metastable NF(b 1 Σ) state.…”
Section: Introductionmentioning
confidence: 99%